PHP 8 Quick Scripting Reference: A Pocket Guide to PHP Web Scripting, Third Edition - Olsson, Mikael (Apress, 2021)
A condensed, code-rich scripting and syntax handbook for the PHP scripting language, this book is packed with useful information and is a must-read for any PHP programmer or web developer. --